Implementasi Metode Pembuktian Terhadap Pelaku Perbuatan Kekerasan Non Fisik (Bullying) Menurut Pasal 80 AYAT (1) Jo Undang-Undang Nomor 35 Tahun 2014 (Studi Di Unit PPA Polres Tulungagung) - effa twintasari; Andreas Andrie Djatmiko (Universitas Tulungagung, 2023)
This writing aims to find out how the method of proof is implemented against the perpetrators of acts of non-physical violence (bullying) according to Article 80 paragraph (1) of Law No. 35 of 2014 and what concrete steps are taken by law enforcers (police) to implement the method of proof against non-physical violence (bullying). This writing research method is qualitative and normative. Data collection techniques include observation, interviews, documentation. With the observation method used by researchers to obtain actual data from the actual conditions that occur. The documentation method itself is used to find data and circumstances related to the object of this research. The results of this study revealed the implementation of the method of proof against the perpetrators of non-physical violence (bullying) and what concrete steps were taken by law enforcers (the police) to implement this method of proving non-physical violence (bullying). letter to the realm of visas This proof is carried out by psychologists, psychiatrists and counselors by conducting interviews with victims of verbal bullying. In addition, the support of those closest to the victim of bullying can also provide positive motivation for the victim to get through it all. If you experience psychological violence, that will be used as evidence later.